Which households use banks? Evidence from the transition economies - Thorsten Beck; Martin Brown (European Central Bank (ECB), 2011)
This paper uses survey data for 29,000 households from 29 transition economies to explore how the use of banking services is related to household characteristics, bank ownership structure and the development of the financial infrastructure. At the household level we find that the holding of a bank account or bank card increases with income, wealth and education in most countries and also find evidence for an urban-rural gap, as well as for a role of religion and social integration. Our results show that foreign bank ownership is associated with more bank accounts among high-wealth, high-income, and educated households. State ownership, on the other hand, does not induce financial inclusion of rural and poorer households. We find that higher deposit insurance coverage, better payment systems and creditor protection encourage the holding of bank accounts in particular by highincome and high-wealth households. All in all, our findings shed doubt on the ability of policy levers to broaden the financial system to disadvantaged groups.
Keywords: G2; G18; O16; P34; 330; Access to finance; Bank-ownership; Creditor protection; Deposit Insurance; Payment system; Bankgeschäft; Konsumentenverhalten; Privater Haushalt; Einlagensicherung; Kreditsicherung; Eigentümerstruktur; Bank; Institutionelle Infrastruktur; Transformationsstaaten